2010
DOI: 10.1155/2010/369549
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MicroRNAs between Eutopic and Ectopic Endometrium in Ovarian Endometriosis

Abstract: Endometriosis, defined as the presence of endometrial tissue outside the uterus, is a common gynecological disease with poorly understood pathogenesis. MicroRNAs are members of a class of small noncoding RNA molecules that have a critical role in posttranscriptional regulation of gene expression by repression of target mRNAs translation. We assessed differentially expressed microRNAs in ectopic endometrium compared with eutopic endometrium in 3 patients through microarray analysis. We identified 50 microRNAs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 60 publications
9
151
3
1
Order By: Relevance
“…Less evidence has demonstrated the roles of miR-126 and Crk in the pathogenesis of EMs. Our present study confirmed that ECs expresses less miR-126 than EUs, further validating the results of previous miRNA profiling studies of EMs [25,[32][33][34]. The present study may provide initial evidence that miR-126 may participate [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Less evidence has demonstrated the roles of miR-126 and Crk in the pathogenesis of EMs. Our present study confirmed that ECs expresses less miR-126 than EUs, further validating the results of previous miRNA profiling studies of EMs [25,[32][33][34]. The present study may provide initial evidence that miR-126 may participate [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, Pan et al (2007) have identified that miR-199a is down-regulated in endometriotic tissues in comparison with normal endometrium. However, down-regulation of miR-199a was not reported by other studies on miRNA expression in endometriosis (Burney et al, 2009;Ohlsson Teague et al, 2009;Filigheddu et al, 2010;Hawkins et al, 2011;Ramon et al, 2011). This is likely due to the difference between the study designs, methods of analysis, menstrual cycle phase at the time of biopsy and patient cohorts used in their study when compared with ours.…”
Section: Discussioncontrasting
confidence: 70%
“…6). MiRNAs are small, non-coding RNAs that are frequently dysregulated in female reproductive pathologies, including endometriosis (Pan et al, 2007;Toloubeydokhti et al, 2008;Burney et al, 2009;Carletti and Christenson, 2009;Ohlsson Teague et al, 2009;Filigheddu et al, 2010;Hawkins et al, 2011;Ramon et al, 2011). In the present report, we observed that the expression level of miR-199a was lower in the eutopic endometrium from women with endometriosis, and even lower in the paired ovarian endometrioma, compared with the expression in normal controls.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Endometriosis affects as many as 10% of all women of reproductive age and is a major cause of pelvic pain and conception delay. Microarray analyses have been employed to identify differentially expressed miRNAs in paired eutopic endometrium and ectopic lesions (Filigheddu et al 2010, Teague et al 2010. Although one study yielded 22 differentially expressed miRNAs and another 50 species, the validity of this approach is somewhat questionable, as endometriotic implants differ profoundly in architecture and cellular composition when compared with eutopic endometrium.…”
Section: Role Of Mirnas In Endometriosismentioning
confidence: 99%